PENGARUH PERSONAL SELLING DAN PELAYANAN TERHADAP KEPUTUSAN MENJADI NASABAH ASURANSI KERUGIAN PADA PT ASURANSI PAROLAMAS CABANG BANDAR LAMPUNG - darmajaya, lp4m ibi (Jurnal Manajemen dan Keuangan, 2011)
PT Asuransi Parolamas an insurance company to combine the elements of marketing mix. Promotion policy does is personal selling and service quality with a prospective customer can take place more intimate and warm. The purpose of this study was to determine the level of influence on personal selling and service of Decision as a customer. The research method used is descriptive method of verification. The population of this study is the customer for General Insurance at Insurance Parolamas UBL branch based on data of 2007-2009 are still active even as many as 3188 customers. The samples were 97 respondents based Slovin formula. Sampling was systematic sampling. The data analysis technique used is multiple linear regression model, the t test and F test. The test results simultaneously or F test concluded that personal selling variables (X1) and services (X2) jointly affect the decision as a customer (Y) at PT. Insurance Branch Parolamas Bandar Lampung, because Fcount (26.074)> Ftable (3.07). Hypothesis test results indicate that partial personal selling (X1) significantly affects the decision as a customer of PT. UBL Branch Parolamas Insurance and services (X2) is also significantly influence the decision as a customer of PT. Insurance Branch Parolamas Bandar Lampung. Keyword: personal selling, service, decree to be customer life insurance.